A New Path Forward: Agriculture and Food Security Strategy for South Sudan - Ogwaro, Betty Achan (2012)
IFPRI Policy Seminar "A New Path Forward: Agriculture and Food Security Strategy for South Sudan" at IFPRI on 23 October 2012 by H.E. Dr. Betty Achan Ogwaro, National Minister of Agriculture and Forestry in the Republic of South Sudan